ثقافة الصورة وأزمات تواجهها في بلاد يوربا: Image culture and the crises encountered in Yoruba Land - Yusuf Onimasa, Abdur-Rauf (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث كان الاتصال بالصورة من تلكم التطورات الحديثة في الأوضاع الإنسانية والاجتماعية التي يشهدها شعوب العالم اليوم من تحوّل لسان التراسل والاتصال من مهارة الكتابة إلى عالم الصورة والألوان، بل صارت الحياة لا ترتاح بدونها فكأنها روح الحياة. ويرى الباحث أن لا بد للمجتمع الإنساني – الذي لا يريد أن يتدهور – أن يتمكن من مواكبة هذا التطور السريع المستمر (ثقافة الصورة) ويتأقلم معه حتى لا يعيش في حالة عزلة من عالمه. ويلاحظ الباحث أن بعض اليوربويين لا يرون للصورة التشكلية سوى المتعة الجمالية فاقتصر اهتمامهم على الجمالي البصري دون غيره. لذلك قام الباحث بهذه الورقة العلمية بقصد إحياء عملية الفن التشكيلي في العالم العربي أجمع وفي بلاد يوربا خاصة، لإبراز بعض الأعمال الفنية التي يشهدها العالم الإنساني اليوم في بلاد يوربا من تصميمات وتصويرات وكاريكاتوريات. ويعتني البحث بتوظيف هذا الفن حيث يوجه الناظر إلى قراءة الصورة قراءة لاحرفية، كما يقرب إلى القراء بعض أزمات أثرت بشكل كبير على سلوكية مجتمع بلاد يوربا في شأن الفن التشكيلي، وأدت هذه الأزمات إلى معارف باطلة وثقافات منحرفة في مفهوم الفن. ويعتمد في ذلك كله على المنهج الوصفي التحليلي. وأخيرا، حصل الباحث على الثقافة التي تحدثه الصور التشكيلية في التعبير بالصور والألوان، كما توصل إلى أن هذه الدراسة تساعد القراء في امتلاك الأدوات الفنية التي يفهمون بها أفكار الصورة. ABSTRACT Communication through images is one of the modern developments in the human and social existence that people of the world are witnessing today, which transforms the language of correspondence and communication from the skill of writing to the world of images and colors. Life has become uncomfortable without them, as if they are the spirit of life. The researcher is of the believe that human society which does not want to deteriorate must be able to keep up with this rapid and continuous development, and adapt to it so that it does not live in isolation from its world. The researcher notes that some Yoruba see nothing but beauty pleasure in the visual image, so their interest was limited to visual aesthetics and nothing else. Therefore, the researcher conducted this research paper with the interest of reviving the process of visual art in the Arab world as a whole and in the Yoruba town in particular, to highlight some of the artistic works that the human world is witnessing today in Yoruba people from designs, photography and caricatures. The research is concerned with employing this art, as it directs the viewer to read the image non-literally. It also brings to the readers some crises that greatly affected the behavior of the Yoruba community regarding visual arts. These crises led to false believes and deviant cultures in the concept of art. In all of this, the researcher relies on the descriptive analytical approach. and finally, the researcher realized the offices that visual images create in expressing images and colors. He also concluded that this study helps readers to possess the artistic tools with which they understand the messages of the image.